Post-harvest Storage and Processing Technologies in Russia: Reducing Yield Loss - Lucas Lima; Tiago Costa; Pedro Silva (Techno Agriculturae Studium of Research, 2024)
Post-harvest losses are a significant challenge in the agricultural sector in Russia, affecting food security and farmers' incomes. Post-harvest storage and processing technologies, such as cold storage and modified atmosphere treatment, have been introduced as solutions to reduce yield loss. However, the effectiveness and adoption of this technology has not been evenly distributed across Russia's agricultural regions. This study aims to analyze the impact of post-harvest storage and processing technologies on the reduction of yield losses in several major agricultural regions in Russia. In addition, this study explores the challenges in the adoption of such technologies by small and medium farmers. This study uses a qualitative descriptive method with a case study approach in several major agricultural regions in Russia. Data were collected through in-depth interviews, questionnaires, and reviews of relevant literature. The analysis was carried out using thematic and descriptive statistical methods to evaluate the effectiveness of the technology in reducing post-harvest losses. The results of the study show that the application of post-harvest storage and processing technology is able to reduce yield losses by up to 50%. However, there is a gap in technology adoption in rural areas that lack supporting infrastructure. Post-harvest storage and processing technologies in Russia have great potential to reduce yield losses and improve food security. Policy and infrastructure support is needed to expand the adoption of these technologies across Russia's agricultural regions.